Education Maintenance Tooth and Mouth on Child School Sari Mulya Village Kindergarten Tebo Regency - Guspianto, Guspianto; Marbun, Merliana; Alista, Rega Veni (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2023)
Dental and oral health problems can have a negative impact on body health and interfere with activities, especially in preschool children. The community service activity aims to provide education to improve knowledge and skills in caring for teeth and mouth in kindergarten school. The partner for this community service activity was Kindergarten School, at Sari Mulya Village, Tebo Regency and was carried out using counseling methods, demonstrations and tooth brushing practices. Counseling can be carried out well and kindergarten children were able to practice how to brush their teeth properly and correctly. It is recommended for schools to carry out "Tooth Brushing Movements" at school regularly.